Modeling the heart defect of transposition of the great arteries using the PHYSBE model - Mohamad Amin, Bakhshali; Daneshvar, Sabalan; Mafi, Mahsa (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/